Health Professionals and hand hygiene: a question of pediatric patient safety - Daisy Zanchi de Abreu Botene; Eva Neri Rubim Pedro
This paper is a qualitative descriptive study, which aims to analyze how the academic education concerning hand hygiene contributes to the pediatric patient safety. This research was developed in an university hospital in Southern Brazil, in the pediatric unit, during the period of August to December, 2012. Sixteen healthcare professionals participated (doctors, nurses and physical therapists). A semi-structured interview was used to gather information. Data was organized by the software QSR Nvivo and analyzed using the content analysis technique. The results allowed us to list two thematic categories: "Hand hygiene and healthcare professionals' academic education"; and "Hand hygiene and professional life". The first thematic category will be presented in this paper. It was identified that the academic education contributes in an ineffective way to the creation of a patient safety culture. According to the professionals, there are gaps during the educational process regarding hand hygiene. The topic is treated in an ineffective and not very significant way to the learning and adhesion of hand hygiene in the professional life. It is recommended that, for the internalization of the practice by future professionals, a transversal, continuous and systematical approach is adopted during the professional's training, evaluations concerning the hand hygiene are done throughout the academic life as well as healthcare professors bethink the topic.